PENGARUH PENGGUNAAN MEDIA VIDEO TERHADAP HASIL BELAJAR SISWA GEOGRAFI PADA KELAS X SMAN 12 SIJUNJUNG - Lara Riskiawati; Dedi Hermon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the low Geography learning outcomes of Grade X students at SMAN 12 Sijunjung due to limited use of instructional media and low student engagement. The objective is to determine the effect of video-based learning media on students’ learning outcomes compared to conventional teaching methods. This research uses a quantitative approach with a quasi-experimental design (nonequivalent control group). The sample consists of two classes: one experimental class using video media and one control class using conventional methods. Data were collected through pre-test and post-test and analyzed using statistical tests (t-test). In conclusion, the use of video media is effective in improving Geography learning outcomes and is recommended for classroom implementation.